2008
DOI: 10.1111/j.1540-4781.2008.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

A DST Model of Multilingualism and the Role of Metalinguistic Awareness

Abstract: This paper suggests that a dynamic systems theory (DST) provides an adequate conceptual metaphor for discussing multilingual development. Multilingual acquisition is a nonlinear and complex dynamic process depending on a number of interacting factors. Variability plays a crucial role in the multilingual system as it changes over time (Herdina & Jessner, 2002). A number of studies on multilingualism have shown that there are qualitative differences between second and third language learning and that these can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
166
0
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(190 citation statements)
references
References 57 publications
5
166
0
19
Order By: Relevance
“…Thus, CAF constructs were integratively and interactively correlated with each other in the participants' L3 writing over time, much in the same way that Yang and Sun (2015) reported about their participant's writing over time. This growth is also consistent with Jessner's model of multilingual development (Jessner, 2008) according to which multilingual learners' L3 undergoes constant increase. Jessner's model also accounts for the backsliding of proficiency in L2 French particularly in terms of fluency which was characterized by a steep decrease starting from semester two.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, CAF constructs were integratively and interactively correlated with each other in the participants' L3 writing over time, much in the same way that Yang and Sun (2015) reported about their participant's writing over time. This growth is also consistent with Jessner's model of multilingual development (Jessner, 2008) according to which multilingual learners' L3 undergoes constant increase. Jessner's model also accounts for the backsliding of proficiency in L2 French particularly in terms of fluency which was characterized by a steep decrease starting from semester two.…”
Section: Discussionsupporting
confidence: 75%
“…Jessner's model also accounts for the backsliding of proficiency in L2 French particularly in terms of fluency which was characterized by a steep decrease starting from semester two. According to Jessner (2008), the persistent growth of L3 occurs in sharp contrast to the decline of L2, resulting in a gradual attrition or loss of L2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a range of studies have demonstrated (e.g. Brophy, 2001;Munoz, 2000;Lasagabaster, 1998;Ringbom, 1987;Thomas, 1998), the positive effects of bilingualism on third language acquisition are attributed to multilingual learners' development of metalinguistic and crosslinguistic awareness (Cenoz, 2003;Jessner, 2006Jessner, , 2008a.…”
Section: The Psycholinguistics Of Tlamentioning
confidence: 99%
“…Moreover, a lot of research in the field seems to have been suffering from a sort of Chomskian hangover, considering language acquisition to be a static, linear phenomenon which is independent from other factors. To date, the dynamism and complexity of multilingualism has been explored from a psycholinguistic perspective (Cenoz, 2000;Herdina & Jessner, 2002;Jessner, 2006Jessner, , 2008bJessner, , 2013 but sociolinguistic research of the same area is in need of additional development (Cenoz, 2013). Furthermore, language attitudes studies which extend beyond Second Language Acquisition (henceforth: SLA) and bilingualism still tend to treat languages separately and maintain a monolingual perspective; holistic approaches to language attitudes are very scarce (Lasagabaster & Safont-Jordà, 2008;Portolés, 2014).…”
Section: Introductionmentioning
confidence: 99%